Sa'adi in the Chain of Prosodic Poets (A Critical Study of the Meters of Sa'adi ’s poetry, Based on Printed Texts and Manuscripts, With a Discussion about Prosodic Poets throughout the History of Persian Poetry) - Mohammadamir Jalali (مطالعات زبانی و بلاغی)
The main topic of this paper is prove that Sa'adi is a prosodic poet. In this article, Saadi's poems are examined from two perspectives on the number of meters and creativity in utilization of meters. The author first proposed two criteria and then introduced the prosodic poets throughout the history of Persian poetry. The main part of this paper has two parts: First, after examining Saadi's poetry and Golestan's poems by using printed text and manuscripts, all the meters of Saadi's poems are shown in a table (41 meters: 13 in Arabic poems and 30 in Persian poems, by lowering 2 common meters). The second part of this article shows Saadi's creativity in Golestan poetry. Too much meters and make new meters by changing the meters of Arabic poetry ("Iranicized meter") and his "musical eloquence" in Golestan's poems, are the reasons to prove that Sa'adi is a prosodic poet. In this paper, the errors of previous researchers have been criticized.